Management of Pediatric Septic Shock and Acute Respiratory Distress Syndrome in Thailand: A Survey of Pediatricians - Puttiteerachot, Pasita; Anantasit, Nattachai; Chaiyakulsil, Chanapai; Vaewpanich, Jarin; Lertburian, Rojjanee; Chantra, Marut (Frontiers in Pediatrics, 2022)
Introduction: Pediatric septic shock and acute respiratory distress syndrome ((pARDS) are major causes of morbidity and mortality in pediatric intensive care units (PICUs). While standardized guidelines for sepsis and pARDS are published regularly, their implementation and adherence to guidelines are different in resource-rich and resource-limited countries. The purpose of this study was to conduct a survey to ascertain variation in current clinician-reported practice in pediatric septic shock and acute respiratory distress syndrome, and the clinician skills in a variety of hospital settings throughout Thailand. Methods: We conducted an electronic survey in pediatricians throughout the country between August 2020 and February 2021 using multiple choice questions and clinical case scenarios based on the 2017 American College of Critical Care Medicine's Consensus guideline for paediatric and neonatal septic shock and the 2015 Pediatric Acute Lung Injury Consensus Conference. Results: The survey elicited responses from 255 pediatricians (125 general pediatricians, 38 pulmonologists, 27 cardiologists, 32 intensivists, and 33 other subspecialists), with 54.5% of the respondents having less than five years of PICU experience. Among the six sepsis scenarios, 72.5% and 78.4% of the respondents had good adherence to the guidelines for managing fluid refractory shock and sedation for intubation, respectively. The ICU physicians reported greater adherence during more complex shock. In ARDS scenarios, 80.8% of the respondents reported having difficulty diagnosing ARDS mimic conditions and used lesser PEEP than the recommendation. Acceptance of permissive hypercapnia and mild hypoxemia was accepted by 62.4% and 49.4% of respondents, respectively. The ICU physicians preferred decremental PEEP titration, whereas general pediatricians preferred incremental PEEP titration. Conclusions: This survey variation could be the result of resource constraints, knowledge gaps, or ambiguous guidelines. Understanding the perspective and rationale for variation in pediatricians’ practices is critical for successful guideline implementation.